The Strategy of Mataram Tourism Services in Growing the Tourism Sector in The Era of COVID-19 - Muhammad Azizurrohman; Muhamad Johari; Sri Ayu Lestari; Hariono Hariono (Universitas Muhammadiyah Yogyakarta, 2022)
COVID-19 has caused numerous disasters in all sectors of the economy, including the tourism industry. Various regions continue to work to restore tourism activities to mitigate the impact that has occurred. This research aims to determine Mataram city tourism's economic recovery strategy during the COVID-19 pandemic. The descriptive qualitative research method was used in this study, with primary and secondary data obtained from the Mataram City Tourism Office, hotels, and restaurants. Data analysis techniques such as data reduction, presentation, and confirmation were used in this study. According to the study's findings, the Mataram City tourism office is attempting to mitigate the impact of COVID-19 through various programs involving tourism stakeholders. These programs include the implementation of CHSE, the creation of unique tours, digital tourism, promotions, and the provision of grants to tourism industry actors.